PENGARUH SYARAT KECAKAPAN UMUM (SKU) PRAMUKA TERHADAP KARAKTER RELIGIUS ANGGOTA PRAMUKA UIN RADEN FATAH PALEMBANG ANGKATAN TAHUN 2018 DAN 2019 - Ariyanto Ariyanto; Mardeli Mardeli; Rohmadi Rohmadi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
Religious character is the value of human attitudes that are closely related to God, personal, fellow human beings, their environment, and freedom formed based on behavior, emotions, and actions based on religion, rules, and community habits. General proficiency requirements (SKU) are a scout training method used either through exams or tests so that participants can get skills according to their needs and get signs of general proficiency. Based on the facts in the field, it shows that there has been a decrease in the religious character of the scout members of UIN Raden Fatah Palembang both, such as when carrying out scouting activities there are still quite a lot of members who leave their religious obligations such as prayer, this incident has shown that the religious character of the members has decreased while the religious character is the initial foundation in preventing evil acts and a good religious character are the beginning of building a good character.This type of research is a quantitative descriptive study using data collection techniques such as documentation, interviews, observation, and questionnaires. The analysis technique used in this study is descriptive analysis, normality test, linearity test, and hypothesis testing using simple regression analysis, testing the correlation coefficient, and calculating the coefficient of determination.Based on the results of the study, it can be concluded that there is an effect of syarat kecakapan umum requirements (SKU) scout on the religious character of scout members of UIN Raden Fatah Palembang based on the results of a simple regression analysis obtained thit> TTAB or 11,991> 2,024, it can be concluded that the accepted hypothesis is Ha and Ho. rejected. The effect of variable X on variable Y is 77.4%, which means it has a high influence and the remaining 22.6% is influenced by other variables.